PERLINDUNGAN HAK ANAK DAN PENCEGAHAN PERILAKU AMORAL: PROTECTION OF CHILD RIGHTS AND PREVENTION OF AMORAL BEHAVIOR - Huda, Ali Anhar Syi’bul; Abdillah, Muhammad Torieq; Prasetia, Trenadi; Vizaini, Akhmad; Soleh, Ridwan M (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
This study aims to determine the contribution of science, such as education and law, in overcoming immoral behavior in the educational world. This study uses qualitative research methods with literature reviews. The results of this research indicate that immoral behavior in education occurs as a result of weak supervision, irresponsibility between different parties in the educational world and religious teaching in learning as a form of overcoming. In fact, the violence in schools is a national problem that must be stopped as it is an attempt to uphold the rights of children as stated in the Child Protection Act. On the other hand, when dealing with immoral behavior that occurs in students, the teacher has the freedom and authority to punish educational behavior. Sanctions can consist of reprimands and/or warnings, both verbally and in writing, but also pedagogical punishments in accordance with the education rules, the teacher's code of ethics and laws and regulations.